Enhancing climate resilience for beans in East Africa through a high-level governments’ participation approach - Kiogora, Joseline; Kagabo, Desire; Byandaga, Livingstone; Mvuyibwami, Patrick (2024)
High-level officials and stakeholders from Kenya and Tanzania gathered in Kagera (Tanzania) and Nakuru County (Kenya) for PICSA master classes conducted by the 'Enhancing Climate Resilience in East Africa (ECREA)' project. The event aimed to enhance farmers' and extension officers' knowledge on how to utilize climate information services to improve their resilience to climate shocks and increase the sustainability of their practices